Relationship of the Vitamin D Receptor and Collagen Iα1 Gene Polymorphisms with Low Bone Mineral Density and Vertebral Fractures in Postmenopausal Turkish Women - Aytün EFESOY,; Özlem YILMAZ,; Gönül ERDEN,; Ali GÜÇTEKİN,; Hatice BODUR,; Metin YILDIRIMKAYA2, (Archives of Rheumatology, 2011)
Objectives: This study aims to investigate (i) the frequencies of the vitamin D receptor (VDR) gene and collagen Iα1 (COL Iα1) gene polymorphisms and (ii) whether there is a relation between the Bsm1 polymorphisms in the VDR gene, and the Sp1 polymorphisms in the COL Iα1 gene and low bone mineral density (BMD), and vertebral fractures in postmenopausal Turkish women. Patients and methods: A hundred postmenopausal Turkish women (mean age 63.4±8.7 years; range 48 to 86 years) who were admitted to our polyclinic for the diagnosis or treatment of osteoporosis were included in this study. The study population was divided into three groups according to the T score value based on BMD measurements. Patients with a T score of >-1.0 formed the control group (n=30). In addition, patients with a T score of <-1.0−>-2.5 formed the osteopenic group (n=30), and those with a T score of <-2.5 formed the osteoporotic group (n=40). The Bsm1 (B/b) polymorphism in the VDR gene and the Sp1 (S/s) polymorphism in the COL Iα1 gene were detected by two parallel polymerase chain reactions and subsequent hybridization. Bone mineral density of the lumbar spine and femur were measured by dual-energy X-ray absorptiometry. Results: The genotype frequencies of the Bsm I (B/b) polymorphism in the VDR gene and the Sp1 (S/s) polymorphism in the COL Iα1 gene were not statistically different among the three study groups. Additionally, no significant difference was found between the patients with vertebral fracture and the patients without fracture in terms of the BB, Bb, and bb genotypes of the VDR gene or in terms of the SS, Ss, and ss genotypes of the COL Iα1 gene. Conclusion: Our findings showed that the Bsm1 polymorphism of the VDR gene and the Sp1 polymorphism of the COL Iα1 gene were not associated with low BMD or vertebral fractures in postmenopausal Turkish women.